2019
DOI: 10.12669/pjms.35.3.29
|View full text |Cite
|
Sign up to set email alerts
|

Use of the surgical safety checklist in the operating room: Operating room nurses’ perspectives

Abstract: Objective: To determine the opinions of operating room nurses towards the Surgical Safety ChecklistTR (SSCTR) and to determine applications for using SSCTR in operating rooms. Methods: This descriptive and cross-sectional study was conducted with 102 nurses working in the operating rooms of a state hospital and a university hospital in the Afyonkarahisar province. Descriptive statistics method were used for data analysis. Results: It was found that all operating room nurses knew the SSCTR and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 18 publications
3
23
0
4
Order By: Relevance
“…However, WHO and the Turkish Ministry of Health underline the importance of assigning one person from the surgical team as a coordinator for the implementation of SSC to achieve complete and error-free surgical procedures (17,48). Previous studies have reported that the responsibility for the implementation of the checklist is generally undertaken by operating room nurses, which is in agreement with the results of our study (30,31,33,37,42). Considering various factors, such as assigning the responsibility of checklist implementation to surgical nurses in addition to their existing duties and the time that should be allocated to the necessary preparations for the next surgery to be performed in the same operating room, it is important for institutions to determine a coordinator for using SSC at all stages for an effective implementation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, WHO and the Turkish Ministry of Health underline the importance of assigning one person from the surgical team as a coordinator for the implementation of SSC to achieve complete and error-free surgical procedures (17,48). Previous studies have reported that the responsibility for the implementation of the checklist is generally undertaken by operating room nurses, which is in agreement with the results of our study (30,31,33,37,42). Considering various factors, such as assigning the responsibility of checklist implementation to surgical nurses in addition to their existing duties and the time that should be allocated to the necessary preparations for the next surgery to be performed in the same operating room, it is important for institutions to determine a coordinator for using SSC at all stages for an effective implementation.…”
Section: Discussionsupporting
confidence: 93%
“…This study findings showed that almost all the healthcare professionals working in surgical units knew about SSC TR . Although this result is consistent with the findings of previous studies (30,31,33,36,37), there are also researchers reporting otherwise. For example, 81.3% of 96 healthcare professionals in a study by Karayurt et al (26) and 23.6% of 208 healthcare professionals in a study by Keskin et al (28) reported that they did not have knowledge of SSC TR (26,28).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The SSC produces numerous benefits that can be broadly characterised into provider benefits (eg, improvements in communication, case understanding and safety culture) and patient benefits (eg, reduced complications or mortality rates). The positive effects of the SSC attenuate when team members are not engaged (eg, when staff fail to answer questions) 9 10. In other words, the SSC’s benefits are not derived from checklist completion alone.…”
Section: Introductionmentioning
confidence: 99%